Forecasting Limited Access to Urology in Rural Communities: Analysis of the American Urological Association Census. Issue 3 (24th May 2019) - Cohen, Andrew J.; Ndoye, Medina; Fergus, Kirkpatrick B.; Lindsey, John; Butler, Christi; Patino, German; Anger, Jennifer T.; Breyer, Benjamin N.
Abstract: Objective: To assess an aging subspecialty workforce and growing population that portends challenges in meeting patient care needs. We hypothesized that rural physicians are retiring at higher rates than their urban counterparts in the United States and that this represents a bellwether for workforce challenges at large. Methods: We analyzed data from the 2014‐2016 American Urological Association Census, a sample‐weighted representative survey of urologists, as a case study for subspecialists. We compared urologists who work in rural regions to nonrural regions on available characteristics. Results: In 2016, rural urologists accounted for 2.4% of 12, 186 practicing urologists in the United States. General urology remained the focus of 90% of rural urologists, compared to 59% of nonrural urologists ( P = .03). Alarmingly, 48% of rural physicians were >65 years old in 2016 compared to 29% in 2014, and 33% of rural urologists were solo practitioners compared to 9% of nonrural urologists ( P < .01). The planned retirement age for rural physicians increased from 68 in 2014 to 73 in 2016 ( P trend = .02). The percentage of rural practice urologists has remained stable since 2014. Conclusions: Rural urologists are older and provide more general urological care than their nonrural counterparts. Rural urologists are postponing retirement. Although this might be due to personal desires and financial goals, it may also be due to a relative absence of potential junior partners. Given that almost 50% of rural urologists were older than 65 in 2016, this is not a sustainable solution to an impending shortage of physicians. Greater innovation in telemedicine or alternative care models will soon be needed.